(untitled) (Journal of Philosophy Culture and Political Science, 2019)
Abstract. This paper analyses the political economy of natural resources literature classifying it on the economic, political, and social aspects regarding institutional interplay. Natural resources might lead to economic prosperity and political development or they destabilize macroeconomic system with windfalls and create political rivalry and social unrest. The specific type of resources matters and makes a difference as well; is it oil or coffee or timber? Institutional development and strategic choices make differences and final outcomes as they determine policies and choices by individual actors. Definitely there are country specific contexts in terms of political culture, demography, historical past and general path dependence but current consensus among researchers is that institutions matter the most. In our paper we look to the different approaches to analyze natural resources in their political and economic parts, and first of all to oil, we look at Dutch disease as a special case of that political and economic interplay. Key words: Kazakhstan, natural resources, political economy, post-Soviet, oil and gas.